Screening for Rubella Antibodies in Normal Pregnant Women and Active Immunization Program in Post Partum Period, A Cost Analysis - Werawatakul, Yuthapong; Sukprasert, Saovaluk; Wongkham, Chamras; Kotimanusvanij, Daroon (Srinagarind Medical Journal, 2013)
During the period from January 1989 to June 1989, 586 normal pregnant women who came for first visit at antenatal care unit, Srinagarind Hospital were screened for rubella antibodies. Rubella hemagglutination inhibition antibody technique was used to detect maternal rubella antibody. 56.7 Percents of them were non immune. Occupation, geographic distribution and general health were statistically significance factors (P<0.05) for rubella immunity. Because of high prevalence of non immunity, active immunization for all women in reproductive age, who do not get pregnant for at least 3 months, would reduce the cost.